Multi-resistant bacteria in spontaneous bacterial peritonitis: A new step in management? - de Mattos, Angelo Alves (Baishideng Publishing Group Inc, 2014)
Spontaneous bacterial peritonitis (SBP) is the most typical infection observed in cirrhosis patients. SBP is responsible for an in-hospital mortality rate of approximately 32%. Recently, pattern changes in the bacterial flora of cirrhosis patients have been observed, and an increase in the prevalence of infections caused by multi-resistant bacteria has been noted. The wide-scale use of quinolones in the prophylaxis of SBP has promoted flora modifications and resulted in the development of bacterial resistance. The efficacy of traditionally recommended therapy has been low in nosocomial infections (up to 40%), and multi-resistance has been observed in up to 22% of isolated germs in nosocomial SBP. For this reason, the use of a broad empirical spectrum antibiotic has been suggested in these situations. The distinction between community-acquired infectious episodes, healthcare-associated infections, or nosocomial infections, and the identification of risk factors for multi-resistant germs can aid in the decision-making process regarding the empirical choice of antibiotic therapy. Broad-spectrum antimicrobial agents, such as carbapenems with or without glycopeptides or piperacillin-tazobactam, should be considered for the initial treatment not only of nosocomial infections but also of healthcare-associated infections when the risk factors or severity signs for multi-resistant bacteria are apparent. The use of cephalosporins should be restricted to community-acquired infections.